Soil and foliar phosphorus determination in Rwanda: Procedures and interpretation - Drechsel, Pay; Mutwewingabo, B; Hagedorn, F; Wortmann, Charles S. (1996)
Revised reference values of available soil phosphorus by Bray I below which bean (Phaseolus vulgaris L.) and sorghum (Sorghum bicolor L.) yield response to applied P is expected, were 6 and 9 ppm, for January and July soil sampling dates, respectively. Reference values determined for interpretation of foliar test results of bean differed from those estimated previously. The critical foliar level of P concentration was estimated to be 0.40%. The importance of modifications of the Bray I procedure for soil P analysis was assessed using the modifications of three soil laboratories in Rwanda. Variations in shaking time, soil to extraction solution ratio, and soil sieve size were found to significantly affect available P values using the Bray I procedure. The modifications of one laboratory gave values which were 75% higher than those of the original Bray I procedure. Errors in preparation of standard solutions and in calculations resulted in values ranging from 2.5 to 300% of the correct value.